2020
DOI: 10.1080/1351847x.2020.1737168
|View full text |Cite
|
Sign up to set email alerts
|

The impact of macroeconomic news on Bitcoin returns

Abstract: This paper examines the relationship between news coverage and Bitcoin returns. Previous studies have provided evidence to suggest that macroeconomic news affects stock returns, commodity prices and interest rates. We construct a sentiment index based on news stories that follow the announcements of four macroeconomic indicators: GDP, unemployment, Consumer Price Index (CPI) and durable goods. By controlling for a number of potential biases we determine as to whether each of the series' have a significant impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 59 publications
3
59
1
Order By: Relevance
“…Wang et al (2020a) show that Bitcoin prices represent noticeably higher trading volume and volatility during hours that occur simultaneously with the daytime trading hours of European and US stock markets. More recently, Corbet et al (2020) investigate the connectedness between news coverage and Bitcoin returns and provide evidence of macroeconomic indicators have a significant effect on Bitcoin returns. They also suggest that the developing cryptocurrency market is further maturing through associations with macroeconomic news.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al (2020a) show that Bitcoin prices represent noticeably higher trading volume and volatility during hours that occur simultaneously with the daytime trading hours of European and US stock markets. More recently, Corbet et al (2020) investigate the connectedness between news coverage and Bitcoin returns and provide evidence of macroeconomic indicators have a significant effect on Bitcoin returns. They also suggest that the developing cryptocurrency market is further maturing through associations with macroeconomic news.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author found significant causation among the variables. Recently, Corbet et al (2020) assessed the relationship between macroeconomic news coverage and Bitcoin returns using regression model and found that the news relating to unemployment and durable goods announcements are found to have significant effect on Bitcoin returns. News relating to GDP and consumer price index do not have significant impact on Bitcoin returns.…”
Section: Review Of Literaturementioning
confidence: 99%
“…These techniques investigate the short-term and long-term relationship between regressors and regress and without taking into account the asymmetric effect for Bitcoin modelling. Corbet et al (2020) pointed out that the Bitcoin price series respond asymmetrically to positive and negative changes in the macroeconomic-financial indicators. Moreover, the pioneering work by Bouri et al (2018) emphasized to apply non-standard (asymmetric) co-integration models to uncover the intricacy and concealed relations between Bitcoin and asset classes.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While the main stream of cryptocurrency research is currently focused on the dilemma as to whether this is a currency or speculative asset (Baur et al [2018]); and conducting analysis of the multiple forms of pricing inefficiencies (Urquhart [2017]; Sensoy [2019]; Mensi et al [2019]; Katsiampa et al [2019]), have provided a concise systematic review of the literature associated with cryptocurrency markets at large, and note that more research is needed to assess environmental and energy use issues. As this new financial product continues to develop through improved market efficiency (Ekinci et al [2019]; Corbet et al [2020b]) and portfolio design (Akhtaruzzaman et al [2019]; Corbet et al [2018]), it is imperative that we continue to understand the true risks associated. While considering the broad improvement in pricing efficiency and market efficiency, indicative of a rapidly developing financial market product, our paper assesses the financial long terms impacts of Bitcoin energy usage.…”
Section: Previous Literaturementioning
confidence: 99%